The Sox17CreERT2 knock‐in mouse line displays spatiotemporal activation of Cre recombinase in distinct Sox17 lineage progenitors. Issue 11 (1st October 2013) - Engert, Silvia; Burtscher, Ingo; Kalali, Behnam; Gerhard, Markus; Lickert, Heiko
Summary The HMG‐box transcription factor Sox17 is essential for endoderm formation, vascular development, and definitive hematopoiesis. To investigate the fate of distinct Sox17‐expressing progenitor cells in a spatiotemporal manner, we generated a hormone‐inducible CreERT2 knock‐in mouse line. By homologous recombination we fused a codon improved, ligand‐dependent estrogen receptor Cre recombinase by an intervening viral T2A sequence for co‐translational cleavage to the 3' coding region of Sox17. Induction of Cre activity by administration of tamoxifen at defined time points of early mouse development and subsequent genetic lineage tracing confirmed the inducibility and tissue specificity of Cre recombination. Furthermore, Cre activity could be selectively induced in extra‐embryonic and embryonic endoderm lineages, the primitive gut tube, and in endothelial cells of the vascular system as well as in the hemogenic endothelium of the dorsal aorta. The Sox17CreERT2 mouse line therefore represents a new tool for genetic lineage tracing in a tissue‐specific manner and in addition enables lineage‐restricted functional analysis. genesis 51:793–802. © 2013 Wiley Periodicals, Inc.